2017
DOI: 10.1080/15265161.2017.1284915
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Genomics and Mental Health Treatment: Setting the Ethical Agenda

Abstract: Realizing the benefits of translating psychiatric genomics research into mental health care is not straightforward. The translation process gives rise to ethical challenges that are distinctive from challenges posed within psychiatric genomics research itself, or that form part of the delivery of clinical psychiatric genetics services. This article outlines and considers three distinct ethical concerns posed by the process of translating genomic research into frontline psychiatric practice and policy making. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 73 publications
0
28
0
Order By: Relevance
“…For example, these conceptual frameworks may engender genetic essentialism —the misguided view that DNA contains the biological, largely immutable “essence” of a disorder, inevitably consigning people with certain genes to the fate of developing a particular health problem (Dar-Nimrod & Heine, 2011; Haslam, 2011). Although the essentialist view that addiction results deterministically from genes may deflect individual blame by countering the notion that people with addictions are simply choosing freely to engage in problematic behaviors, it may also promote the notion that people with genetically caused disorders lack agency or control over their behavior, and are thus helpless against their symptoms (Dar-Nimrod, Zuckerman, & Duberstein, 2013; Kong, Dunn, & Parker, 2017; Meurk et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…For example, these conceptual frameworks may engender genetic essentialism —the misguided view that DNA contains the biological, largely immutable “essence” of a disorder, inevitably consigning people with certain genes to the fate of developing a particular health problem (Dar-Nimrod & Heine, 2011; Haslam, 2011). Although the essentialist view that addiction results deterministically from genes may deflect individual blame by countering the notion that people with addictions are simply choosing freely to engage in problematic behaviors, it may also promote the notion that people with genetically caused disorders lack agency or control over their behavior, and are thus helpless against their symptoms (Dar-Nimrod, Zuckerman, & Duberstein, 2013; Kong, Dunn, & Parker, 2017; Meurk et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Jordan has been a refugee hosting country for many years including large influxes of Iraqis and now Syrians, which requests to the Health Sector Working Group to conduct research studies, that are frequent and often based on the needs/interests of researchers and not on research gaps identified by operational agencies (Campbell et al, 2015;Kong, Dunn, & Parker, 2017;Shen et al, 2017;Vaz & Srinivasan, 2014). Furthermore, to date, there have been few measures beyond standard ethical review procedures to ensure that specific protection or ethical concerns relating to people with mental health problems or refugees are considered in planning and conducting and reporting research.…”
Section: The Case Of Jordanmentioning
confidence: 99%
“…As laudable as this aim is, how its goals and aspirations are to succeed in the global context is a significant concern for two reasons: first, psychiatric genomics will not be practically applicable if there is little engagement with a range of ethical issues that are raised in this approach; second, there is a risk that ethical violations could occur in research and application if these issues are not examined carefully. The ethics of psychiatric genomics from local and global perspectives has garnered little systematic attention thus far (Kong, Dunn, & Parker, ), though increased ethical attention on the implications of psychiatric genomics in the American context has been particularly welcome in current projects funded by the National Human Genome Research Institute's Ethical, Legal and Social Implications (ELSI) Research Program.…”
Section: Introduction/rationalementioning
confidence: 99%